Region-Dependent Increase of Cerebral Blood Flow During Electrically Induced Contraction of the Hindlimbs in Rats - Chaney, Remi; Garnier, Philippe; Quirié, Aurore; Martin, Alain; Prigent-Tessier, Anne; Marie, Christine (Frontiers in Physiology, 2022)
Elevation of cerebral blood flow (CBF) may contribute to the cerebral benefits of the regular practice of physical exercise. Surprisingly, while electrically induced contraction of a large muscular mass is a potential substitute for physical exercise to improve cognition, its effect on CBF remains to be investigated. Therefore, the present study investigated CBF in the cortical area representing the hindlimb, the hippocampus and the prefrontal cortex in the same anesthetized rats subjected to either acute (30 min) or chronic (30 min for 7 days) electrically induced bilateral hindlimb contraction. While CBF in the cortical area representing the hindlimb was assessed from both laser doppler flowmetry (LDFCBF) and changes in p-eNOSSer1177 levels (p-eNOSCBF), CBF was evaluated only from changes in p-eNOSSer1177 levels in the hippocampus and the prefrontal cortex. The contribution of increased cardiac output and increased neuronal activity to CBF changes were examined. Stimulation was associated with tachycardia and no change in arterial blood pressure. It increased LDFCBF with a time- and intensity-dependent manner as well as p-eNOSCBF in the area representing the hindlimb. By contrast, p-eNOSCBF was unchanged in the two other regions. The augmentation of LDFCBF was partially reduced by atenolol (a ß1 receptor antagonist) and not reproduced by the administration of dobutamine (a ß1 receptor agonist). Levels of c-fos as a marker of neuronal activation selectively increased in the area representing the hindlimb. In conclusion, electrically induced bilateral hindlimb contraction selectively increased CBF in the cortical area representing the stimulated muscles as a result of neuronal hyperactivity and increased cardiac output. The absence of CBF changes in cognition-related brain regions does not support flow-dependent neuroplasticity in the pro-cognitive effect of electrically induced contraction of a large muscular mass.